Life Practices on Social Media of Minority’s Generation Z in Turkey during the COVİD-19 Period - KOÇ, REZAL (ADAMOR Toplum Araştırmaları Merkezi, 2021)
The COVID-19 pandemic has caused and continues to cause uncertainty around the world. It is a traumatic event that psychologically affects all segments of society. However, particularly the young and disadvantaged in a society like minorities, refugees and disabled people may face even harsher problems. The youngest generation to witness this traumatic event is generation Z. Individuals of this generation came to the world in a period when communication technologies have experienced tremendous growth and progress, thus making them carry characteristics which are very different from other generations. Since this generation is still very young, it is challenging to obtain academic data on them. Studies on this generation are just being conducted, and the number of scientific studies in this field is still minimal. However, what stands out in the already existing research is that social media is an integral part of their lives. While there are many studies on social media usage habits and the effects of these during the pandemic, the research done on minorities in society during this period does also not stand out in the literature. Therefore, this study focuses on an even smaller fraction of the already tiny fraction (0,2%) of non-Muslim minorities in Turkey; the Syriac generation Z in Turkey. Using the method of online surveys, this study demonstrated that all of the surveyed members of the Syriac generation Z, in Turkey connect to the internet, use social media and follow COVID-19 related news on social media on a daily basis. The study also revealed that they spend more time on social media than before COVID-19 and frequently communicate with their friends on social media. Furthermore, this study found that during the COVID-19 period, the surveyed members of the Syriac generation Z were more anxious and generally preferred spending time with their hobbies as well as communicating with their friends and families as a method of coping with their concerns. Also, half of the surveyed members stated that social media helped relieve their concerns during this period.
Türkiye’de Azınlık Z Kuşağının Covid-19 Döneminde Sosyal Medya ile Yaşam Pratikleri
Keywords: Covid-19; Social Media; Minorities; Coping; Generation Z